The Impact of Ownership Types on the Value of Discretionary Accruals: What is the Role of Audit Committee? Evidence from Pakistan - Khan, Sattar; Kamal, Yasir; Khan, Azhar; Hussain, Arif; Rafiq, Muhammad; Bibi, Maryam; Shah, Syed Fahad Ali; Shah, Zahir; Khan, Muhammad (International Journal of Economics and Financial Issues, 2020)
The research paper attempts to investigate the connection between Ownership Structure and Audit Committee Effectiveness on discretionary accruals in Pakistan. This study analyzed 5 years of data over the period of 2013 to 2017 of 169 listed firms of the Pakistan Stock Exchanges (PSX). The data is panel and it is analyzed with the fixed-effect regression to check the association between ownership structure and audit committee effectiveness on discretionary accruals. The findings of this article show that the effectiveness of an audit committee is very instrumental in bringing down the value of discretionary accruals. This paper confirms the view that audit committee effectiveness mitigates discretionary accruals in PSX listed firms, Furthermore, this study found no clue that blocks ownership, management ownership, foreign ownership and institutional ownership constrain discretionary accruals. To the best of researchers' knowledge, this empirical study is first of its kind in Pakistan. The present research study recommended and supports the recent amendment in Pakistan Corporate Governance Code about audit committee independence and expertise for reducing discretionary accruals. Keywords: Ownership Types, Audit Committee Effectiveness, Corporate Governance, Discretionary Accruals, Pakistan Stock Exchange JEL Classifications: G34, M4 DOI: https://doi.org/10.32479/ijefi.10081